Marketing Strategy for Technological Start-ups - Sceulovs, D.; Rustenova, A.J.E. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the article contemporary marketing strategies in technological start-ups applied in Europe are considered, a characteristics of technological start-ups is given in order of importance, taking into account innovation and knowledge management, the major challenges of technological start-ups in EU are evaluated and the most effective contemporary marketing strategies are determined. The key characteristics of technological start-ups have been identified and categorized with the aim to develop key components to which it is necessary to focus for better and more effective marketing. Due to the problem of limiting resources and high research costs current marketing strategies have been developed and expanded with the fast technologies and financing in the start-up industry. The crucial elements for developing the marketing strategy has been identified and explained. The marketing strategy development from transactional and relationship points of view is discussed and finally the extent of marketing strategy practice in technological start-ups in Europe has been established.
Технологиялық стартаптарды іске қосу үшін маркетингтік стратегия
Маркетинговая стратегия для технологических стартапов
Keywords: marketing; start-up; strategy; business model; technology; innovation; project; modernization; management; product